Understanding Variety of Languages as an Effort to Prevent Hate Speech in Students of Senior High School State 2 Dewantara - Trisfayani; Syahriandi; Masithah Mahsa; Radhiah; Rani Ardesi Pratiwi; Safriandi (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2022)
This community service activity is motivated by several things. First, the number of students who use sarcastic language style, both on social media and in daily life. Second, students' impoliteness in communicating in the school environment, with colleagues, class seniors, and teachers. Third, students begin to have difficulty distinguishing the placement of language use, which language can be used in formal or informal situations. Fourth, many students are not able to filter information properly so some of them spread false information (hoaxes) and hate speech. Based on these reasons, training is needed that aims to improve students' understanding of various languages in an effort to prevent hate speech. The method used in this community service is the lecture, training, and dialogical method. The lecture method is used to convey material related to filtering information and using good language in social media. The training method is carried out by involving participants directly to identify and correct sentences that are not in accordance with norms and violate the ITE Law. Meanwhile, the dialogical method was applied in overcoming the problems experienced by the participants during the training. The targets in this training are students of SMAN 2 Dewantara. The benefit of this training is to increase students' understanding of various languages as an effort to prevent hate speech. Not only that, students will be more familiar with the ITE Law and be wiser in using language on social media.